2008
DOI: 10.1210/en.2007-1597
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Protection of Estrogen against Gastric Acid-Induced Duodenal Injury: Stimulation of Duodenal Mucosal Bicarbonate Secretion

Abstract: Because human duodenal mucosal bicarbonate secretion (DMBS) protects duodenum against acid-peptic injury, we hypothesize that estrogen stimulates DMBS, thereby attributing to the clinically observed lower incidence of duodenal ulcer in premenopausal women than the age-matched men. We found that basal and acid-stimulated DMBS responses were 1.5 and 2.4-fold higher in female than male mice in vivo, respectively. Acid-stimulated DMBS in both genders was abolished by ICI 182,780 and tamoxifen. Estradiol-17beta (E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 67 publications
4
66
0
1
Order By: Relevance
“…All experiments were performed with adult Harlan C-57 black mice; homozygous CFTR knockout (CFTR Ϫ/Ϫ ) mice and their wild-type littermates (CFTR ϩ/ϩ ), which were established as described previously (13); and mice deficient in KCNQ1 (kcnq1 Ϫ/Ϫ ) and their wildtype littermates (kcnq1 ϩ/ϩ ), which were generated as described earlier (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All experiments were performed with adult Harlan C-57 black mice; homozygous CFTR knockout (CFTR Ϫ/Ϫ ) mice and their wild-type littermates (CFTR ϩ/ϩ ), which were established as described previously (13); and mice deficient in KCNQ1 (kcnq1 Ϫ/Ϫ ) and their wildtype littermates (kcnq1 ϩ/ϩ ), which were generated as described earlier (14).…”
Section: Methodsmentioning
confidence: 99%
“…We found that although cyclic AMP plays a major role in intestinal Cl Ϫ secretion, Ca 2ϩ signaling may be critical for transepithelial HCO 3 Ϫ secretion (13). However, activation of most well defined receptors expressed in intestinal epithelial cells usually increase both [Ca 2ϩ ] cyt and intracellular cyclic AMP levels, making it difficult to distinguish between [Ca 2ϩ ] cyt -and cyclic AMP-regulated epithelial ion transports.…”
mentioning
confidence: 90%
“…Also, previous studies have shown that peptic ulcer is more common in men than women. Therefore, it is rational to infer that, similar to other organs, E2 and progesterone may have protective effects in GI tract, and E2 plays a protecting role against acid-peptic duodenal injury in females [47]. Steroid hormones, in particular progesterone and estrogen, have effects on the gastric motility and secretions [19], and are also involved in the pathogenesis of some functional disorders in the gut [20].…”
Section: Tbi Gi Tract and Sex Hormonesmentioning
confidence: 99%
“…Studies have shown that pregnant women or women taking oral contraceptive pills (estrogen/progesterone compounds) exhibited a reduced frequency of duodenal ulcer [73]. Furthermore, duodenal ulcer runs a more serious course in postmenopausal than premenopausal women [47]. Finally, clinical observations showing that pregnant women with high estrogen levels of placental origin hardly develop ulcers and women taking oral contraceptives experience a significantly decreased incidence of ulcers [73], strongly support the protective role of estrogen in the duodenum [3].…”
Section: Tbi Gi Tract and Sex Hormonesmentioning
confidence: 99%
See 1 more Smart Citation